2010
DOI: 10.1136/thx.2009.125443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atopy and asthma on exhaled nitric oxide in an unselected birth cohort study

Abstract: Background Asthma is considered to be associated with elevated levels of exhaled nitric oxide (FeNO). The nature of this relationship and how it is influenced by atopy are still not resolved. Methods The Isle of Wight birth cohort (N¼1456) was reassessed at 18 years of age. Participants able to attend the research centre were assessed by questionnaires, skin prick testing and FeNO in order to explore the interrelationship between asthma, atopy and FeNO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
100
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 32 publications
23
100
1
1
Order By: Relevance
“…Hence, eNO may be elevated in allergic rhinitis patients that do not have concomitant asthma, which suggests that physicians should see whether patients have allergic rhinitis when they use NO as diagnostic tools of asthma or monitoring tools of treatment efficacy. Scott et al [11] showed that atopy was significantly associated with higher levels of eNO. They reported that the level of eNO in non-atopic asthmatic participants was no different from that in the non-atopic non-asthmatic group and concluded that eNO behaves as a biomarker of atopy and of the "allergic asthma" phenotype, rather than of asthma itself.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, eNO may be elevated in allergic rhinitis patients that do not have concomitant asthma, which suggests that physicians should see whether patients have allergic rhinitis when they use NO as diagnostic tools of asthma or monitoring tools of treatment efficacy. Scott et al [11] showed that atopy was significantly associated with higher levels of eNO. They reported that the level of eNO in non-atopic asthmatic participants was no different from that in the non-atopic non-asthmatic group and concluded that eNO behaves as a biomarker of atopy and of the "allergic asthma" phenotype, rather than of asthma itself.…”
Section: Discussionmentioning
confidence: 99%
“…Participants attending in person also performed spirometry, bronchodilator reversibility (BDR) to 600 mg inhaled salbutamol, fractional exhaled nitric oxide (FeNO) measurement, methacholine challenge test and skin prick test (SPT). Identical methodology, published previously [30], was used for spirometry and challenge testing at 10 and 18 yrs. FeNO (Nioxmino1, Aerocrine AB, Solna, Sweden) and SPT to common food and aeroallergens (ALK-Abello, Horsholm, Denmark) were performed as reported previously [30].…”
Section: Methodsmentioning
confidence: 99%
“…Identical methodology, published previously [30], was used for spirometry and challenge testing at 10 and 18 yrs. FeNO (Nioxmino1, Aerocrine AB, Solna, Sweden) and SPT to common food and aeroallergens (ALK-Abello, Horsholm, Denmark) were performed as reported previously [30].…”
Section: Methodsmentioning
confidence: 99%
“…The authors found that low FeNO levels (<22.5 ppb), normal sputum eosinophils (<2.5%) and absence of atopy suggested a lower probability of CRC (19). Many studies reported the association between FeNO levels and atopy with increasing threshold for FeNO levels in atopic asthmatic subjects both in adults (22) and in children (23).…”
mentioning
confidence: 99%